(untitled) (Semiárida, 2020)
The Irrigation District of Cipolletti (38° 56 ’South latitude and 68° 00’ West longitude) is one of the districts of the Upper Valle del Río Negro, an extensive area of agriculture under irrigation. It is managed by a consortium of irrigators, whose function is to operate and maintain a system dating from the early twentieth century, with marked deficiencies in its infrastructure and low application efficiencies. The objective of this work was to improve the efficiency values of application in the plot, from a deficit irrigation that does not produce stress in the crop. This form of irrigation consists in reducing the irrigation sheet in certain periods of the crop, ensuring that for these conditions, the tensions in the root zone are within the ranges suggested for maximum water extraction. The tool used was the HYDRUS1D simulation model (Simunek et al., 2013). This model allowed to model different alternatives of deficit irrigation, depending on the moment and the sheet applied. The results indicate that the most convenient alternative was that which reduced the application sheet in stage I by 60% (initial stage of slow growth), 20% in stage II (rapid growth) and 90% in the period postharvest